2013
DOI: 10.1038/ajg.2012.465
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cancer in Patients With Autoimmune Pancreatitis

Abstract: Patients with AIP are at high risk of having various cancers. The highest risk for cancer in the first year after AIP diagnosis and absence of AIP relapse after successful treatment of the coexisting cancers suggest that AIP may develop as a paraneoplastic syndrome in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
215
5
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(241 citation statements)
references
References 37 publications
6
215
5
5
Order By: Relevance
“…Concerning AIP and total malignancy, it is also difficult to draw any specific conclusions given our current understanding. In light of the results of two reports [14,16], however, it seems unlikely that AIP is responsible for the increased risk of total malignancy. Shiokawa et al…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Concerning AIP and total malignancy, it is also difficult to draw any specific conclusions given our current understanding. In light of the results of two reports [14,16], however, it seems unlikely that AIP is responsible for the increased risk of total malignancy. Shiokawa et al…”
Section: Discussionmentioning
confidence: 86%
“…If 100 patients with AIP are necessary to identify one case of pancreatic cancer and the SIR is 3.6, as per our previous report [14], a sample of approximately 450 patients is necessary to demonstrate statistical significance [15]. It is possible that the SIR is much \ 3.6 [16]. Thus, large-scale nationwide research is required to resolve this problem.…”
Section: Aip and Pancreatobiliary Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies evaluating the SIR support the association between IgG4-RD and total malignancies (16,17). Yamamoto et al reported the SIR for total malignancies to be 3.8 in their series, which consisted primarily of patients with Mikulicz's disease (16), while Shiokawa et al reported the SIR to be 2.7 in their series, which consisted of AIP patients only (17).…”
Section: Discussionmentioning
confidence: 98%
“…However, there is very limited data on the incidence of malignancy in AIP. Shiokawa et al [46] reported that patients with AIP are at high risk of having various cancers. e highest risk for cancer in the rst year a er AIP diagnosis and absence of AIP relapse a er successful treatment of the coexisting cancers suggest that AIP may develop as a paraneoplastic syndrome in some patients.…”
Section: Discussionmentioning
confidence: 99%